Psychological features of the family education styles demonstration in the development of the emotional and wilful sphere for senior preschool children - Журат, Ю.В. (My University, 2023)
THE ARTICLE PRESENTS THE RESULTS OF A THEORETICAL AND EMPIRICAL STUDY OF THE FAMILY UPBRINGING STYLES INFLUENCE ON THE EMOTIONAL AND WILFUL SPHERE FOR OLDER PRESCHOOLERS. THE THEORETICAL SUBSTANTIATION OF THE PROBLEM CONCERNS THE ISSUES OF DETERMINING THE PARENTING STYLES CHARACTERISTICS, WHICH PROVIDE FOR THE PURPOSEFUL EDUCATIONAL INFLUENCE OF PARENTS WITH THE AIM OF FORMING CERTAIN QUALITIES AND SKILLS IN THE CHILD. IT IS NOTED THAT AN IMPORTANT FEATURE OF THE FAMILY IS THAT THE CHILD STAYS IN IT FOR A LONG TIME OF HIS/HER LIFE. DEPENDING ON THE SPECIAL EDUCATIONAL SIGNIFICANCE OF THE FAMILY, THE PROBLEM ARISES OF HOW TO ACT IN ORDER TO MAXIMIZE THE POSITIVE AND MINIMIZE THE NEGATIVE INFLUENCE OF THE FAMILY ON THE CHILD UPBRINGING. IN THIS REGARD, IT IS NECESSARY TO ACCURATELY DETERMINE THE INTRA-FAMILY, SOCIAL AND PSYCHOLOGICAL FACTORS THAT HAVE EDUCATIONAL SIGNIFICANCE FOR THE CHILD. THE MAIN DIRECTION OF THE EMOTIONAL DEVELOPMENT IN PRESCHOOLERS IS THE ABILITY TO MANAGE EMOTIONS, THAT IS, THE SKILLS OF VOLUNTARY BEHAVIOUR. ANOTHER DIRECTION IS RELATED TO THE FACT THAT EMOTIONS BECOME STABLE, ACQUIRE GREAT DEPTH AND APPEAR HIGHER FEELINGS AS COMPASSION, EMPATHY.
Keywords: EMOTIONAL AND WILFUL SPHERE; STYLES OF FAMILY UPBRINGING; EMOTIONAL WELL-BEING